Importance of mineralogy in geometallurgy: application in Peru - Espinoza S., Luis A. (2021)
The contribution of mineralogy is essential in modern mining studies. Its importance lies in the qualification of mineral deposits and in what has been designated as process mineralogy, this concept has taken force due to the different uses in the processing of mineral deposits. Mineralogical studies provide information on the different classes of minerals and their peculiarities. This provides information to explain the results obtained in the different metallurgical tests and determine the potential that could affect the processing. As it is decisive to establish the disposition of the minerals in the deposit, we need to apply the different mineralogical characterization methods such as X-ray diffractometry, electron microscopy (microprobe and scanning), optical microscopy, among others. These resources are used together, being complementary to obtain complete information. This research allows to evaluate the role of mineralogy in geometallurgy, characterization methods; cases applied in Au leaching and copper flotation at the national level. The importance of mineralogical characterization is highlighted to establish what will be the metallurgical behavior of the minerals to be processed.